The Effect of Green Supply Chain Management on Organizational Environmental Performance (Starbucks Case Study in The City of Bandung) - Bangun Munthe (Jurnal Mamangan, 2024)
This study examines the influence of Green Supply Chain Management (GSCM) on organizational environmental performance in Starbucks coffee shops in Bandung City, Indonesia. The coffee shop industry has a high impact on the environment due to its use of plastic packaging. Starbucks, being one of the most popular coffee brands in Indonesia, has taken steps to implement "go green" and reduce plastic waste. The study explores the effect of four factors - Internal Green Supply Chain Management, Environmental Monitoring of Suppliers, Environmental Collaboration with Customers, and Environmental Performance - on the perspective of Starbucks employees. The results show that all four variables are categorized as very good or strongly agreed, with an overall score of 87-88%. The study's findings provide insights into the benefits of GSCM, such as reducing waste and cost, improving environmental performance, and enhancing a company's image and marketing exposure. This research is useful for writers and entrepreneurs in the coffee shop industry, though it is limited to Starbucks outlets in Bandung City.